2007
DOI: 10.1007/s11262-007-0110-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of a Chinese isolate of Getah-like virus and its phylogenetic relationship with other Alphaviruses

Abstract: An alphavirus, M-1 strain, was isolated from a pool of culicine mosquitoes collected in Hainan island of China during an arbovirus survey in 1964. In the present study, we determined the complete nucleotide sequence of the M-1 strain using RT-PCR and RACE techniques. The M-1 genome is 11,690 nucleotides (nt) in length and contains two open reading frames (ORFs) encoding four nonstructural proteins and five structural proteins, respectively. Searches using Blast and comparison analyses suggested that M-1 is clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Previous studies have shown that the genomes of several GETV strains contain insertions or deletions in proteincoding or noncoding regions (Wen et al 2007, Zhai et al 2008). However, we found no insertions or deletions in the genome sequence of strain 12IH26.…”
Section: Analysis Of Getv Genome Sequence and Phylogenetic Characterimentioning
confidence: 99%
“…Previous studies have shown that the genomes of several GETV strains contain insertions or deletions in proteincoding or noncoding regions (Wen et al 2007, Zhai et al 2008). However, we found no insertions or deletions in the genome sequence of strain 12IH26.…”
Section: Analysis Of Getv Genome Sequence and Phylogenetic Characterimentioning
confidence: 99%
“…As shown in Figure 1A, its genome is a positive, single strand RNA, which encodes several structural and non-structural proteins 3 . In the previous study, we identified and characterized alphavirus M1 as a naturally existing oncolytic virus for the reason that M1 virus can selectively replicate in cancer cells and destroy them without causing excessive damage to normal tissues 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…M1 is an alphavirus isolated in the 1960s from the Hainan province of China, and belongs to the Togavirus family of viruses [15]. The genome of M1 is 11,690 nucleotides (nt) in length and contains two open reading frames, encoding four nonstructural proteins (nsP1-nsP2-nsP3-nsP4), and five structural proteins (C-E3-E2-6K-E1) [15]. What's more, the direct cell lytic effect of M1 is through prolonged and severe Endoplasmic reticulum(ER) stress induced apoptosis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%